CESifo World Economic Survey August 2013 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe; Timo Wollmershäuser (CESifo World Economic Survey, 2013)
World Economic Climate: World economic climate clouds over slightly - Economic Expectations: remain positive - Inflation: Different price trends - Currencies: US dollar expected to rise - Interest Rates: Long-term interest rates likely to rise - Special Topic: Tax administration and tax competition between countries
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies